A model study to determine engineering properties of peat soil and effect on strength after stabilisation - Hashim, Roslan; Islam, M.S. (2008)
Objective of this study is to determine various engineering properties of peat soil and to observe effect on strength after stabilisation by soil-cement column technique. Some field and laboratory study was conducted to find engineering properties of peat soil and to stabilise peat soil collected from Peninsular, Malaysia. A set of fabricated mixing tools and tools for injecting binder were used in this experiment. Ordinary Portland cement, bentonite and well graded sand were used as binder. Unconfined compression test was performed to observe effect in unconfined compressive strength after stabilisation. The test was conducted after 1day, 3 days, 7days and 28 days to examine the effect of curing time on strength. Mixing quality and formation of column was observed by visual inspection. It was observed that the unconfined compressive strength of stabilised column was increased considerably. It was also found that strength increased with increasing in curing time.